Early‐life gut microbiome and egg allergy. Issue 7 (15th March 2018) - Fazlollahi, M.; Chun, Y.; Grishin, A.; Wood, R. A.; Burks, A. W.; Dawson, P.; Jones, S. M.; Leung, D. Y. M.; Sampson, H. A.; Sicherer, S. H.; Bunyavanich, S.
Abstract: Background: Gut microbiota may play a role in egg allergy. We sought to examine the association between early‐life gut microbiota and egg allergy. Methods: We studied 141 children with egg allergy and controls from the multicenter Consortium of Food Allergy Research study. At enrollment (age 3 to 16 months), fecal samples were collected, and clinical evaluation, egg‐specific IgE measurement, and egg skin prick test were performed. Gut microbiome was profiled by 16S rRNA sequencing. Analyses for the primary outcome of egg allergy at enrollment, and the secondary outcomes of egg sensitization at enrollment and resolution of egg allergy by age 8 years, were performed using Quantitative Insights into Microbial Ecology, Phylogenetic Investigation of Communities by Reconstruction of Unobserved States, and Statistical Analysis of Metagenomic Profiles. Results: Compared to controls, increased alpha diversity and distinct taxa (PERMANOVA P  = 5.0 × 10 −4 ) characterized the early‐life gut microbiome of children with egg allergy. Genera from the Lachnospiraceae, Streptococcaceae, and Leuconostocaceae families were differentially abundant in children with egg allergy. Predicted metagenome functional analyses showed differential purine metabolism by the gut microbiota of egg‐allergic subjects (Kruskal‐Wallis P adj  = 0.021). Greater gut microbiome diversity and genera from Lachnospiraceae and Ruminococcaceae were associated with egg sensitization (PERMANOVA P  = 5.0 × 10 −4 ). Among those with egg allergy, there was no association between early‐life gut microbiota and egg allergy resolution by age 8 years. Conclusion: The distinct early‐life gut microbiota in egg‐allergic and egg‐sensitized children identified by our study may point to targets for preventive or therapeutic intervention.